Reducing vulnerability to forced labour and trafficking of women migrant workers from South- to West-Asia - ElDidi, Hagar; van Biljon, Chloe; Alvi, Muzna; Ringler, Claudia; Ratna, Nazmun N.; Abdulrahim, Sawsan; Kilby, Patrick; Wu, Joyce; Choudhury, Zahid ul Arefin (Informa UK Limited, 2023)
Millions of short-term, low-skilled women migrant workers from South-Asia to West-Asia experience exploitative and unsafe conditions. We review evidence from literature and interview 18 key informants to assess the exploitation migrant women face, and highlight the impacts of past interventions to determine their potential, and realised effectiveness, in reducing forced labour and trafficking. We find that women face varied precarious situations along the migration pathway, including interactions with recruiters in the home country, incurring debt, pre-departure formalities and training, withheld wages and mobility restrictions. We discuss varying degrees of success of mechanisms that aim to reduce vulnerability to forced labour.